Permanent Pace Maker Lead Vegetation along with Tricuspid Valve Leaflets Involvement - A Case Report - Fatema, Nilufar; Sultana, Nazneen; Deeba, Sahajadi Farah; Ahmad, CM; Rahman, Fazlur; Siddique, Md Abu; Banerjee, Sajal K; Sultan, Md Ashraf Uddin (University Heart Journal, 2013)
Permanent pace maker (PPM) lead vegetation is a rare condition. Diagnosis is made by persistent fever after PPM lead implantation, blood culture,2D & M-mode Echocardiography and confirmed by Transoesophageal echocardiography. Many literatures showed that Staphylococcus epidermidis is the most responsible organism as it can grow on plastic material. In this case, we confirmed the vegetations in PPM lead and Tricuspid valve (TV) leaflets by Transoesophageal echocardiography. DOI: http://dx.doi.org/10.3329/uhj.v8i2.16088 University Heart Journal Vol. 8, No. 2, July 2012